Formation of Tobolsk Classical Hymnasium in First Decade of 19th Century - M. Yu. Lapteva; A. A. Valitov; D. Yu. Fedotova (Научный диалог, 2021)
The article is devoted to the study of material, financial, personnel problems that accompanied the process of restructuring the system of Russian secondary education in Western Siberia in the first decade after the beginning of reforms in the field of education in 1803—1804. Based on the specific historical material of the history of the Tobolsk classical gymnasium, the first in Western Siberia, the author considers ways to overcome these problems during the period of the reform of the Main Public School and the formation of a male classical gymnasium on its basis. Special attention is paid to the issues of administrative and financial support of the first Western Siberian classical gymnasium by the trustee of the Kazan educational district S. Ya. Rumovsky, Minister of Education P. V. Zavadovsky, administrative and economic activities of the first director of the gymnasium A. Kh. Eiben, issues of charity of Russian and local entrepreneurs. The research was carried out on the basis of published and unpublished archival materials. The first group should include a historical note about the Tobolsk gymnasium, compiled by teachers S. I. Zamakhaev and G. A. Tsvetaev in 1889 on the basis of the archive of the gymnasium, now lost. Specific historical, systemic, comparative historical methods have become the main methods for researching sources.